Solar UVR sensitivity of phyto- and bacterio-plankton communities from Patagonian coastal waters under increased nutrients and acidification - Durán Romero, Cristina (2017)
The effects of ultraviolet radiation (UVR) under future expected conditions of acidification and increase in nutrient inputs were studied on a post-bloom phytoplankton and bacterioplankton community of Patagonian coastal waters. We performed an experiment using microcosms where two environmental conditions were mimicked using a cluster approach: present (ambient nutrients and pH) and future (increased nutrients and acidification), and acclimating the samples for five days to two radiation treatments (full solar radiation [+UVR] and exclusion of UVR [–UVR]). We evaluated the short-term (hours) sensitivity of the community to solar UVR through chlorophyll a fluorescence parameters (e.g. the effective photochemical quantum yield of PSII [ΦPSII]) at the beginning, at the mid-point and at the end of the acclimation period. Primary production and heterotrophic bacterial production (HBP) were determined, and biological weighting functions were calculated, at the beginning and at the end of the acclimation period. Mid-term effects (days) were evaluated as changes in taxonomic composition, growth rates and size structure of the community. Although the UVR-induced inhibition on ΦPSII decreased in both clusters, samples remained sensitive to UVR after the 5 days of acclimation. Also, under the future conditions, there was, in general, an increase in the phytoplankton carbon incorporation rates along the experiment as compared to the present conditions. Bacterioplankton sensitivity to UVR changed along the experiment from inhibition to enhancement of HBP, and future environmental conditions stimulated bacterial growth, probably due to indirect effects caused by phytoplankton. Those changes in the microbial loop functioning and structure under future global change conditions might have important consequences for the carbon pump and thus for the carbon sequestration and trophodynamics of Patagonian coastal waters.